Antagonizing CD105 and androgen receptor to target stromal-epithelial interactions for clinical benefit - Smith, Bethany N.; Mishra, Rajeev; Billet, Sandrine; Placencio-Hickok, Veronica R.; Kim, Minhyung; Zhang, Le; Duong, Frank; Madhav, Anisha; Scher, Kevin; Moldawer, Nancy; Oppenheim, Amy; Angara, Bryan; et al. (Molecular therapy, 2023)
Androgen receptor signaling inhibitors (ARSIs) are standard of care for advanced prostate cancer (PCa) patients. Eventual resistance to ARSIs can include the expression of androgen receptor (AR) splice variant, AR-V7, expression as a recognized means of ligand-independent androgen signaling. We demonstrated that interleukin (IL)-6-mediated AR-V7 expression requires bone morphogenic protein (BMP) and CD105 receptor activity in both PCa and associated fibroblasts. Chromatin immunoprecipitation supported CD105-dependent ID1- and E2F-mediated expression of RBM38. Further, RNA immune precipitation demonstrated RBM38 binds the AR-cryptic exon 3 to enable AR-V7 generation. The forced expression of AR-V7 by primary prostatic fibroblasts diminished PCa sensitivity to ARSI. Conversely, downregulation of AR-V7 expression in cancer epithelia and associated fibroblasts was achieved by a CD105-neutralizing antibody, carotuximab. These compelling pre-clinical findings initiated an interventional study in PCa patients developing ARSI resistance. The combination of carotuximab and ARSI (i.e., enzalutamide or abiraterone) provided disease stabilization in four of nine assessable ARSI-refractory patients. Circulating tumor cell evaluation showed AR-V7 downregulation in the responsive subjects on combination treatment and revealed a three-gene panel that was predictive of response. The systemic antagonism of BMP/CD105 signaling can support ARSI re-sensitization in pre-clinical models and subjects that have otherwise developed resistance due to AR-V7 expression. [Display omitted] Neil Bhowmick and colleagues found that targeting CD105 with carotuximab, inhibiting bone morphogenic protein signaling, affected a recognized hormone therapy resistance. Combining carotuximab with hormone therapy limited tumor progression in mouse models as well as supporting progression-free survival of patients determined to be resistant to hormone therapy alone.